2022
DOI: 10.3389/feart.2022.839712
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Back-Arc Closure Phases of the East Sea: Stratigraphic Evidence From the SW Ulleung Basin Margin

Abstract: This study focuses on revisiting the tectostratigraphic framework of the Ulleung Basin and conceptualizing neotectonics around the western East Sea margin. Based on the analysis of 2D and 3D multi-channel seismic reflection data and offshore drill wells, we divided the entire sedimentary successions of the Ulleung Basin into four tectostratigraphic sequences, named TS1 (c. 23–16 Ma), TS2 (c. 16–9 Ma), TS3 (c. 9–4 Ma), and TS4 (c. 4 Ma–present), in ascending order. The results show that each sequence has been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…In contrast to the eastern margin, broadly accepted as a plate boundary undergoing SI, the western margin has been regarded as a stable intraplate setting that has been tectonically dormant. However, an increasing amount of evidence points toward that the western East Sea margin as well is in the compressional neotectonic regime (Choi et al., 2008; Kim, Moon, et al., 2016; Kim, Rhie, et al., 2016; Kim, Yoon, et al., 2018; Kim, Ree, et al., 2018; Lee et al., 2022). Recent seismic reflection investigation has demonstrated that the western PDZ of the East Sea was reactivated into an incipient subduction zone under a regional E–W compressional stress regime since the Early Pliocene (Kim, Yoon, et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast to the eastern margin, broadly accepted as a plate boundary undergoing SI, the western margin has been regarded as a stable intraplate setting that has been tectonically dormant. However, an increasing amount of evidence points toward that the western East Sea margin as well is in the compressional neotectonic regime (Choi et al., 2008; Kim, Moon, et al., 2016; Kim, Rhie, et al., 2016; Kim, Yoon, et al., 2018; Kim, Ree, et al., 2018; Lee et al., 2022). Recent seismic reflection investigation has demonstrated that the western PDZ of the East Sea was reactivated into an incipient subduction zone under a regional E–W compressional stress regime since the Early Pliocene (Kim, Yoon, et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The tectonic inversion lasted for approximately 7 myr until the early Late Miocene (Lee et al., 2022), which formed a series of the Dolgorae‐San'in Thrust‐Fold Belt (Yamamoto, 1993) and the Tsushima‐Goto islands (Fabbri et al., 1996; Kim et al., 2008). Following tectonic inversion, the entire East Sea region experienced slow subsidence by thermal contraction of the back‐arc lithosphere and loading of thickly accumulated sedimentary succession (Ingle, 1992; Jolivet & Tamaki, 1992; Kim et al., 2013; Lee et al., 2022). At present, the East Sea sits within an E–W compressional regime since the Early Pliocene (c. 4 Ma) (Taira, 2001).…”
Section: Regional Settingmentioning
confidence: 99%
See 3 more Smart Citations